Cap binding-independent recruitment of eIF4E to cytoplasmic foci - Ferrero, Paola Viviana (2012)
Eukaryotic translation initiation factor 4E (eIF4E) is required for cap-dependent initiation. In addition, eIF4E occurs in cytoplasmic foci such as processing bodies (PB) and stress granules (SG). We examined the role of key functional amino acid residues of eIF4E in the recruitment of this protein to cytoplasmic foci. We demonstrate that tryptophan residues required for mRNA cap recognition are not required for the recruitment of eIF4E to SG or PB. We show that a tryptophan residue required for protein-protein interactions is essential for the accumulation of eIF4E in granules. Moreover, we show, by the analysis of two Drosophila eIF4E isoforms, that the tryptophan residue is the common feature for eIF4E for the transfer of active mRNA from polysomes to other ribonucleoprotein particles in the cytoplasm. This residue resides in a putative interaction domain different than the eIF4E-BP domain. We conclude that protein-protein interactions rather than interactions with the mRNA are essential for the recruitment of eIF4E and for a putative nucleation function.